Meiofauna abundance in the German exploration area for polymetallic nodule mining, Clarion Clipperton Fracture Zone, Pacific - Uhlenkott, Katja; Vink, Annemiek; Kuhn, Thomas; Martínez Arbizu, Pedro (In: Uhlenkott, K et al. (2020): Meiofauna abundance and distribution predicted with random forest regression in the German exploration area for polymetallic nodule mining, Clarion Clipperton Fracture Zone, Pacific [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.912217, 2020)
The dataset contains counts of meiofauna organisms on high taxonomic level.
Keywords: meiofauna